The Islamic Movement at Khairun University Ternate - Muhammad Irfan Syuhudi (Balai Penelitian dan Pengembangan Agama Semarang, 2015)
This article aims to describe Islamic religious thought of Muslim student at KhairunUniversity in Ternate and the dynamic of religious movement organizations on campus. Informants of this study were selected using purposive method including activists of Islamic organizations, students, and lecturers of the university. Data were collected using interviews, observation, and documentation, and searching data related to social context of the study from the internet. Findings of the research shows that the type of religious understanding and nationality of Muslim students after the reformation era at Khairun University began experiencing a shift since the presence of trans-national organizations, such as the Indonesian Muslim Student Action Union (KAMMI), Campus Propagation Institute (LDK), Hizbut Tahrir (HT), and Wahdah Islamiyah (WI). Those organizations adopt fundamentalists thought who want purification of Islam, and anti-tradition. Nationality thought adopted by these organizations is a country that imposes Islamic law and Establishes a state of Khilafah (HT). Nevertheless, most students at the Khairun University embrace cultural Islam, following the footsteps of their parents and Ternate society in general.